Obesity and food marketing: a narrative review of consumer influence, regulatory gaps, and ethical implications - Farzand, Anam; Rohin, Mohd Adzim Khalili; Awan, Sana Javaid; Hussain, Ahram; Faizan, Muhammad; Ahmad, Abdul Momin Rizwan (Frontiers in Nutrition, 2025)
BackgroundObesity is a multifactorial global health crisis exacerbated by modern food marketing strategies that encourage the consumption of energy-dense, nutrient-poor (EDNP) foods. Children and socio-economically disadvantages groups are particularly vulnerable to the cognitive and emotional cues embedded in food advertising.ObjectivesTo investigate the ethical aspects of marketing to vulnerable groups, evaluate the shortcomings of the current regulatory frameworks, critically analyze the impact of food marketing on consumer behavior and dietary patterns, and offer policy-relevant insights for public health interventions. Methods: Multidisciplinary sources from the fields of public health, behavioral psychology, marketing science, and nutrition policy were synthesized through an extensive narrative review. Through methodical searches of databases such as PubMed, Scopus, Web of Science, and Google Scholar, peer-reviewed and gray literature were found. Among the theoretical models used are the REFCAM model, the Theory of Planned Behavior, and the Social Cognitive Theory.ResultsFood marketing uses digital microtargeting, sensory cues, and psychological priming to influence consumption. Overconsumption has become commonplace due to strategies including portion control, manipulating brand loyalty, and health halo benefits. Despite global variation in regulatory responses, corporate lobbying, disjointed governance, and inadequate digital oversight often limit their effectiveness. Marketing aimed at minorities and children raises ethical concerns, as there is proof of exploitation through deceptive and culturally specific advertising. Comparative case studies highlight regulatory achievements (like Chile and France) as well as failures (like UK policy delays).ConclusionFood marketing is a major contributor to the development of obesogenic environments, despite being poorly controlled. A change from reactive to proactive, system-level governance is necessary to combat obesity. Strong digital control, more stringent nutrient profiling, and a moral shift in food marketing strategies are all part of this. Promoting healthy choices and safeguarding vulnerable people require cross-sectoral collaboration.